Constructivist or Christian: A Mixed-Methods Examination of Teacher Purposes and Practices at Mennonite Schools. Issue 1 (2nd January 2021) - Yoder, Paul J.; Wiens, Peter D.; Chou, Annie
Abstract: Christian educators must regularly articulate the ways in which they add value to the learning experiences of students, recognizing that pedagogy and purpose are inextricably linked. This study investigates the relationship between constructivist teaching practices and the religious beliefs of Christian educators. Drawing on mixed-methods analysis of survey data, the study includes 385 teachers in a network of private preK-12 Mennonite schools stretching from Oregon to Pennsylvania to Florida. Data analysis suggests that while the participants consistently espouse a high level of commitment to Christian approaches to education, the participants' relationship to constructivist pedagogy across the corpus is less clear. The results contribute to the empirical literature on faith integration and notions of constructivism in Christian education.